Recent Advances in Presentation, Diagnosis and Treatment for Mixed Vaginitis - Qi, Wenhui; Li, Huanrong; Wang, Chen; Li, Huiyang; Zhang, Bingbing; Dong, Mengting; Fan, Aiping; Han, Cha; Xue, Fengxia (Frontiers in Cellular and Infection Microbiology, 2021)
Mixed vaginitis is the simultaneous presence of at least two types of vaginitis, contributing to an abnormal vaginal milieu and leading to vaginal symptoms and signs. However, associations between symptoms and the type of mixed vaginitis have not been clearly elucidated, and research on mixed vaginitis is still in the preliminary stage. Therefore, the pathogenic mechanism of mixed vaginitis remains understudied. Mixed vaginitis generally involves the formation of mixed biofilms. The study of polymicrobial interactions and mixed biofilms will provide a new idea for the understanding of mixed vaginitis. Moreover, this review summarizes some effective management and laboratory diagnosis of mixed vaginitis to avoid inappropriate therapy, recurrence, and reinfection. It is of high clinical importance to obtain relevant clinical data to improve clinical knowledge about mixed vaginitis.